1998
DOI: 10.1002/(sici)1096-9136(199808)15:8<688::aid-dia649>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and hyperinsulinaemia in adult life

Abstract: To explore the relation between reduced fetal growth and impaired glucose tolerance in adult life, an oral glucose tolerance test (75 g glucose) was carried out on 218 men and women, now aged around 50 years, who had been measured in detail at birth. Measurements of plasma concentrations of glucose and insulin were made at 0, 30, and 120 min. Fasting plasma concentrations of proinsulin and 32-33 split proinsulin were also measured. People in the highest category of birthweight tended to have the lowest plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 10 publications
0
19
1
Order By: Relevance
“…A number of studies have now shown that birthweight is inversely associated with the risk of developing a number of disorders in adult life, including coronary heart disease, 1,2 hypertension, 3 noninsulin dependent diabetes [4][5][6] and syndrome X. 7 Obesity and a central pattern of fat distribution are important risk factors for these disorders.…”
Section: Introductioncontrasting
confidence: 63%
“…A number of studies have now shown that birthweight is inversely associated with the risk of developing a number of disorders in adult life, including coronary heart disease, 1,2 hypertension, 3 noninsulin dependent diabetes [4][5][6] and syndrome X. 7 Obesity and a central pattern of fat distribution are important risk factors for these disorders.…”
Section: Introductioncontrasting
confidence: 63%
“…To these we can now add high PAI-1 activity, a mediator of impaired fibrinolysis. The relations of low birth weight with a high waist:hip ratio and truncal subcutaneous fat distribution, present in this study, have in previous studies been inconsistent [8,26,27] and less frequently investigated [15], respectively. Low birth weight predicts a smaller hip but not a larger waist in this study and thus the inverse relation of birth weight with the waist:hip ratio does not reflect an association with central adiposity.…”
Section: Discussionmentioning
confidence: 98%
“…Some 3,4,7 but not all 5,11,14 previous studies that have examined the relationship between birth weight and waist -hip ratio have found a small inverse association after adjustment for current body size. Law et al 3 interpreted this association as evidence of a link between fetal growth and abdominal fatness.…”
Section: Discussionmentioning
confidence: 99%